“La cultura de la sexualidad en los estudiantes de Educación Básica”. - Freire Tapia, Rosa Marina (2020)
The research that is carried out addresses the following scientific problem: How to favor the culture of sexuality in Basic Education students?, and in order to solve the problem, the development of a pedagogical strategy to favor the culture of sexuality is projected as a general objective. sexuality in students of Basic Education. From the assumption of a mixed research approach, theoretical, empirical, statistical methods and research techniques are used. Intentionally, a sample of 30 Basic Education students was selected to carry out the diagnosis, results that justify the proposed strategy, which becomes an option for the development of the culture of sexuality in Basic Education students. It allows to work in an organized way the essential contents of the referred topic and to involve all those involved in the process, as demonstrated by the results obtained as part of the final finding, it allows the author to give a partial solution to the problem that gave rise to the investigation and demonstrate that the strategy facilitates the development of the culture of sexuality in students of Basic Education.